The supratemporal system and the pattern of ramification of cephalic sensory canals in Denticeps clupeoides (Denticipitoidei, Teleostei): additional evidence for monophyly of Clupeiformes and Clupeoidei - Di Dario, Fabio; de Pinna, Mário C. C. (Papéis Avulsos de Zoologia, 2006)
The cephalic portions of the latero-sensory canal system in Denticeps clupeoides are described and analyzed. The species, a small herring-like fish from relictual West African streams, is the most primitive living clupeomorph and sole Recent representative of suborder Denticipitoidei. As sister group to over 360 species in Clupeoidei, Denticeps is a key taxon in understanding clupeomorph and lower teleostean relationships. Observations on recently-collected specimens of Denticeps clupeoides revealed comparatively-important and previously-unrecorded details of the cephalic latero-sensory canals which are relevant for understanding relationships at different levels in clupeomorph phylogeny. The infraorbital, supraorbital, preopercular, extrascapular and post-temporal canals of Denticeps have unbranched tubules in soft tissue, as in the hypothesized plesiomorphic condition for lower teleosts. Contrastingly, the presence of a complex network formed by a high order of branching of cephalic canals is hypothesized as a synapomorphy of the Clupeoidei. Denticeps and the Clupeoidei share an exclusive sensory branch that originates at the junction between the extrascapular bone and the recessus lateralis, here hypothesized as an additional synapomorphy of Clupeiformes. A supratemporal system is newly recorded in Denticeps, and the character is proposed as a synapomorphy of Clupeiformes, and not of Clupeoidei as previously thought. The hypothesis that the supratemporal system is homologous to the supraorbital cavern is refuted, and the latter is corroborated as an autapomorphy of Denticeps. Another autapomorphy of Denticeps (or Denticipitoidei) is the presence of the postorbital bulla, a hitherto unrecorded specialization of the infraorbital canal associated with infraorbitals 4 and 5. Homologies of other tubules of the cephalic sensory canals in Denticeps are also discussed, with emphasis on their bearing on the recognition of homologies of infraorbital bones in Denticeps and other lower teleosts. In general, data from the cephalic latero-sensory system corroborate Denticeps as the sister group to all other Recent clupeomorphs, and provide additional support for the monophyly of Clupeoidei and Clupeiformes.